Caspase‐3 regulates the migration, invasion and metastasis of colon cancer cells. Issue 4 (30th March 2018) - Zhou, Min; Liu, Xinjian; Li, Zonghai; Huang, Qian; Li, Fang; Li, Chuan‐Yuan
Abstract : Caspase‐3 ( CASP3 ) is a major mediator of apoptosis activated during cellular exposure to cytotoxic drugs, radiotherapy or immunotherapy. It is often used as a marker for efficacy of cancer therapy. However, recent reports indicate that caspase‐3 has also non‐apoptotic roles such as promotion of tumor relapse and tumor angiogenesis. Therefore, the roles of caspase‐3 in tumor progression remain to be defined clearly. In our study, we established caspase‐3 knockout (KO) colon cancer cell lines by use of the CRISPR technology. In vitro, caspase‐3 knockout HCT116 cells were significantly less clonogenic in soft agar assays. They were also significantly less invasive and more sensitive to radiation and mitomycin C than control cells. In vivo, CASP3KO cells formed tumors at rates similar to control cells but were significantly more sensitive to radiotherapy. They were also less prone to pulmonary metastasis when inoculated either subcutaneously or intravenously. At the mechanistic level, caspase‐3 gene knockout appeared to cause reduced EMT phenotypes when compared to parental HCT116 cells. Indeed, they showed significantly increased E‐cadherin expression, reduced N‐cadherin, Snail, Slug and ZEB1 expression than control cells. Therefore, therapeutic targeting of caspase‐3 may not only increase the sensitivity of cancer cell to chemotherapy and radiotherapy, but also inhibit cancer cell invasion and metastasis. Abstract : What's new? The main function of caspase‐3 is to eliminate damaged cells. Following activation, it cleaves proteins vital to cell function, thereby fueling apoptosis. As a result, caspase‐3 generally is thought to be a beneficial factor in cancer therapy. This study shows, however, that caspase‐3 plays important roles in promoting colon cancer cell invasion and metastasis. Compared to control cells, caspase‐3 knockout colon cancer cells (CASP3KO) demonstrated significantly reduced invasive potential in vitro . In vivo, tumors formed by CASP3KO cells exhibited increased sensitivity to radiotherapy and reduced metastatic tendency. The findings suggest that caspase‐3 is a potential target for colon cancer therapy.